Inquiry Based Learning with OE3R Strategy and Its Impact on Students' Mastery of Basic Concepts of Analytical Chemistry - Pradita Rahmadhani; Sutrisno Sutrisno; Hayuni Retno Widarti (Jurnal Pendidikan Sains, 2020)
Abstract: The purpose of implementation of OE3R Strategy on lecturing Fundamental of Analytical Chemistry are to determine differences in students’ conceptual understanding achievements. This researchidesigniusingiaiQuasi-experimental (one group pre-test-post-test) with different treatment for both groups. The Experimental Group learns using OE3R Strategy, then the Control Group using the conventional strategy. The subject of research was a student in Fundamental of Analytical Chemistry courses in the Chemistry Department State University of Malang. The result shows that inquiry-based learning with OE3R Strategy as innovation learning effective to make differences of students’ conceptual understanding achievements on Fundamental of Analytical Chemistry courses.Abstrak: Implementasiistrategi OE3R pada matakuliahiDasar-dasar KimiaiAnalitik bertujuan untuk mengetahui perbedaan hasil penguasaanikonsep mahasiswa. Desainipenelitian ini menggunakan quasy-experimental (one group pretest-posttest) dengan perlakuan berbeda pada keduaikelompok. Pada kelompokieksperimen dibelajarkan dengan strategi OE3R, sedangkan pada kelompokikontrol menggunakan strategiikonvensional. Subjek penelitian ini adalah mahasiswa peserta matakuliahiDasar-dasar KimiaiAnalitik di Jurusan Kimia Universitas Negeri Malang. Hasilipenelitian menunjukkan bahwa pembelajaran berbasisiinkuiri dengan strategi OE3R sebagai sebuah inovasiipembelajaran efektif untuk membuat perbedaan pada hasil penguasaanikonsep pesertaididik pada matakuliahiDasar-dasar KimiaiAnalitik.